Seasonal changes in energy allocation to somatic and reproductive body components of the common cold temperature sea urchin Loxechinus albus in a Sub-Antarctic environment - Pérez, Analía Fernanda; Morriconi, Elba Rosa; Boy, Claudia Clementina; Calvo, Jorge (Polar Biology)
Monthly variations in the somatic indexes and energetic content of organs were investigated in Loxechinus albus from the Beagle Channel. Samples were collected monthly from May 2004 to May 2005. Lantern and test indexes did not vary significantly. A major peak of gonad index (GI) was observed in winter (sexual maturation period), with a strong declination in November suggesting a spawning period in spring. In coincidence a shortening of feeding activities was expressed by the lower values of gut index (Gut I), suggesting that the gut is a storage organ. The values of gonad energetic content (GEC) and total gonad energetic content (TGEC) showed minimum values in winter (ripe stage) and the maximum in spring (spawned stage). The TGEC reached higher monthly average values (50-200 kJ) than total gut energetic content (TGuEC) (20-40 kJ). These differences indicate that the gonads constitute the most important store organs in L. albus. Moreover, organic stores are built up in the gonads after spawning, and then utilized during gamete production. Fil: Pérez, Analía Fernanda. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Morriconi, Elba Rosa. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Boy, Claudia Clementina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Calvo, Jorge. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina